Семантика границы и проблема идентичности в романе Алексея Поляринова Кадавры - Dvorecka, Inna (Studia Rossica Posnaniensia, 2026)
The research object of this article is the new novel by Alexei Polyarinov, Cadavers (2024), which has sparked much debate. While critical reviews focus on defining the genre and intertextual connections of the text, this article analyses a key element in the artistic world of Polyarinov’s novel – the category of border, which is introduced in its titular image and realised at different levels of the artistic system, explaining its multi-layered nature and raising the issue of identity as the (in)ability to belong to a particular group. The border has structure-forming significance for the main categories of the artistic world of the text: space, time, and man. On an ontological level, the central image of the novel – the cadaver – is a sign of the disruption of the borders between the world of the living and the dead, a catastrophic shift in the very foundations of existence. In the spatial paradigm, the breakdown of the world order manifests itself in signs of degradation (political, economical, ecological, social, and interethnic) in cities of southern Russia. A slight temporal shift (the novel is set in 2027) places all the depicted events in a dystopian world of ongoing catastrophe, isolated from reality, which enables a detailed examination of the logic of its internal existence. Finally, the forms of existence in such a world are demonstrated by the character system. While the majority prefers to ignore the trouble, the disruption of normal life is felt most acutely by people with distorted identities who cannot find their place in the world, remaining frozen in an uncertain position ‘in between’. Thus, the catastrophic nature of the experience depicted by the author becomes not only a theme, but also a central feature of the novel’s artistic world.